Shallow subaqueous to emergent intra-caldera silicic volcanism of the Motuoapa Peninsula, Taupo Volcanic Zone, New Zealand: new constraints from geologic mapping, sedimentology and zircon geochronology - Kósik, Szabolcs; Németh, Károly; Danišík, Martin; Procter, Jonathan N.; Schmitt, Axel Karl; Friedrichs, Bjarne; Stewart, Robert B. (Journal of volcanology and geothermal research, 2021)
Motuoapa Peninsula, located in the southeast of the Taupo Volcanic Centre, New Zealand, is dominated by a silicic pyroclastic cone and overlaying lavas. The pyroclastic succession has not been recognised and studied before, and its thickness and sedimentological characteristics indicate completely different eruption mechanisms than proposed for the other pyroclastic successions within the central Taupo Volcanic Zone. Here, we present the results of field mapping and sedimentological characterisation of accessible pyroclastic deposits, and complement these data with combined U-Th and (U-Th)/He zircon geochronology providing first constraints on the succession's crystallization and eruption history. (U-Th)/He zircon eruption ages of 77.2 ± 6.3, 81.3 ± 9.2 and 34.5 ± 3.1 ka indicate that volcanic activity in the Motuoapa Peninsula occurred in two distinct eruptive episodes that were separated by ca. 45 kyrs. The earlier rhyolitic eruption at ca. 80 ka is inferred to have commenced in a shallow subaqueous environment. Its lowermost succession includes breccias and tuff breccias sourced from an extruding lava dome by autobrecciation, quench-fragmentation and localised debris flows. With gradual emergence of the growing volcanic pile, explosive hydrovolcanic activity became dominant, constructing an emergent cone by pyroclastic density currents and fall-out. The lack of exotic/accidental clasts, along with an abundance of low-vesicularity rhyolitic juvenile fragments, suggests fragmentation driven by magma-water interaction, which predominantly occurred at shallow depths within the outgassed part of the ascending magma. The frequency and thickness of ash-dominated units increases upwards, suggesting a gradual increase in explosive energy of tephra jets. The final phase of the rhyolitic activity was dominated by emplacement of viscous lava that breached the crater rim and flowed onto the SE sector of the pyroclastic cone. The remnant of the Motuoapa pyroclastic cone, along with the bedded structure of deposits that comprise fallout and surge-dominated units, appears very similar to Surtseyan tuff cones and silicic tuff/pumice cones described elsewhere. A dacitic eruption that produced a nearby lava dome at ca. 35 ka, represents a significantly younger event that occurred after substantial erosion of the earlier pyroclastic cone. The Motuoapa Peninsula deposits most likely record the evolution of a subaqueous silicic eruption, where hydrovolcanism played a fundamental role on subaerial pyroclastic cone formation in a terrestrial environment with abundant surface water availability. The similarities between the environment of the Taupo area today and the area during the Motuoapa activity at ca. 80 ka may provide an analogue model for future subaqueous eruptions in the region.